Cash transfers and multiplier effect: lessons from the grain subsidy program in China. Issue 1 (1st February 2016) - Yi, Fujin; Lu, Wuyi; Zhou, Yingheng
Abstract : Purpose: – The purpose of this paper is to examine the multiplier effects of the grain subsidy program in China, which is a large food self-sufficiency project that is implemented as a cash transfer program. Income multiplier effects have not been empirically examined in the evaluation of the grain subsidy program although increasing the income of farmers is the original goal of this project. Design/methodology/approach: – A large number of household-level observations are employed to measure the program's income multiplier. An unrestricted model was first employed to measure the multipliers in a period of two years, and the difference was evaluated. Then, the income promotion effects of grain subsidy on various income sources for each specific subset of the population, such as liquidity conditions and household characteristics, were estimated. Findings: – The results show that the grain subsidy program has a high income multiplier, and the income promotion effect of the transferred subsidies is from agricultural production derived by intensifying input for each unit of land. The multiplier effect of the grain subsidy program as a cash transfer program can be interpreted as the shadow value of relaxing liquidity constraints and could be particularly utilized by households with more farming land and farmers in less developed regions in China. Hence, to maximize the income multiplier effect, the grain subsidy distribution method should consider these criteria instead of retaining the prevalent standard that is based on contracted land areas. Originality/value: – This study addresses the gap that the effect of China's grain subsidy program on income increment has not been empirically examined in nation wide.